Frying performance of red palm olein, RBD and corn oil. - Thed, S.T.; Wong , K.F. (1996)
Red palm olein is a new cooking oil produced in Malaysia. It is carefully processed with stringent quality control to preserve the inherent high contents of B-carotene, tocopherols, and tocotrienols. The high level of natural antioxidants found in red palm olein would contribute to its thermal stability and the antioxidants could also be adsorbed or absorbed into the foods during frying,thereby enhancing the keeping quality of the fried foods. A comparative study was therefore undertaken to evaluate the frying performance of red palm olein,RBD (refined,bleached, and deodorised) palm olein and corn oil. The quality changes of various oil samples during frying at 180C for 3 hr per day for 5 consecutive days were monitored. Thiobarbituric acid (TBA) value,free fatty acids content (FFA),iodine value,color and viscosity of the oil samples were determined. Sensory quality of the prawn crackers fried in these oils and their oxidative stability were also examined. Red palm olein exhibited significantly better oxidative and hydraulic stability during frying (a=0.05). At the end of frying period,TBA values were 54.0,60.9 and 65.8 umoles malonaldehydes/kg oil,while FFA were 0.42,0.48 and 0.53% for red palm olein,RBD palm olein and corn oil respectively. The iodine values decreased by 8.6,9.4 and 16.9g of i2/100g oil,while viscosity increased by 16.8,21.0 and 28.2 centipoise for red palm olein,RBD palm olein and corn oil,respectively.